2021
DOI: 10.1371/journal.pcbi.1008670
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the dynamics of cerebellar Purkinje cells through the interaction of excitatory and inhibitory feedforward pathways

Abstract: The dynamics of cerebellar neuronal networks is controlled by the underlying building blocks of neurons and synapses between them. For which, the computation of Purkinje cells (PCs), the only output cells of the cerebellar cortex, is implemented through various types of neural pathways interactively routing excitation and inhibition converged to PCs. Such tuning of excitation and inhibition, coming from the gating of specific pathways as well as short-term plasticity (STP) of the synapses, plays a dominant rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 85 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…As a result, GC oscillations are mediated by GoCs, consistent with other modeling work [ 19 ]. Furthermore, our findings of tuning GC oscillations by different formats of GoC inhibition suggest that downstream Purkinje cells, that receive inputs from GCs as the output of the granular layer, could show coherent oscillations [ 19 , 47 ]. Additional modulation sent out from Purkinje cells can further play a functional role in regulating synchronization of other brain areas [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, GC oscillations are mediated by GoCs, consistent with other modeling work [ 19 ]. Furthermore, our findings of tuning GC oscillations by different formats of GoC inhibition suggest that downstream Purkinje cells, that receive inputs from GCs as the output of the granular layer, could show coherent oscillations [ 19 , 47 ]. Additional modulation sent out from Purkinje cells can further play a functional role in regulating synchronization of other brain areas [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oscillations require precise synaptic integration to allow neurons to fire within a confined time window. However, the nonlinear characteristic of short-term plasticity (STP) disrupts precise synaptic integration, produces jitters to spike time, and depresses the synchrony of the network activity [47] (see S4 Fig) . Here we modeled the STP using a classic phenomenological model [40,41] (see Methods) and installed it on GoC-GC synapses showing both facilitation and depression with repeated incoming spikes (S5 Fig). Indeed, we found that network oscillations of GC responses were distorted by the STP of GoC-GC synapses in feedback inhibition networks (Fig 3).…”
Section: Network Oscillation Depressed By Short-term Plasticity Of Goc-gc Synapsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the dynamics of the neural network is controlled by multiple layers and pathways [ 65 , 66 ]. In some neural systems, feedforward networks are more prominent.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal adaption is ubiquitous not only for the neural computation of sensory input, 43 but also for controlling and adjusting the dynamic range of single cells and neural populations in investigations of general neural dynamics. 70,71 Without limitation of the properties of visual stimulus, e.g., spatial invariation, our importance index, an important feature for modeling of the retinal encoding, used to evaluate the temporal filter enables us to incorporate neuronal adaption in response to complex and dynamic natural visual scenes. 72,73 Thus, our filter pruning approach could help reduce the effective number of parameters in other deep-learning models while processing the dynamic visual scenes, expanding their performance beyond that for static natural images.…”
Section: Model Parameter Pruning Using Temporal Filtersmentioning
confidence: 99%